2016
DOI: 10.5539/elt.v9n6p189
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Critical Thinking and EFL Learners’ Speaking Ability

Abstract: The current study sought to investigate the relationship between critical thinking and speaking ability among EFL students at Payame Noor University (PNU) of Rasht. This research concerned determining the fact that whether language students who are as critical thinker, perform better in their speaking ability or not. In order to answer the research question and test the hypothesis, 100 PNU English students were selected by applying IELTS speaking test as the samples of this study. Then in order to figure out c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 14 publications
2
24
0
2
Order By: Relevance
“…Thestudy conducted by Baghaei and Riasati (2013) suggests that the the creativity of the teachers may affect the achievement of students. Additionally, Ramezani, Larsari, and Kiasi (2016) find that English learners having higher critical thinking had better speaking skill.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Thestudy conducted by Baghaei and Riasati (2013) suggests that the the creativity of the teachers may affect the achievement of students. Additionally, Ramezani, Larsari, and Kiasi (2016) find that English learners having higher critical thinking had better speaking skill.…”
Section: Introductionmentioning
confidence: 80%
“…Therefore, this research focuses on the neglected influence of students' creativity to construct sentences toward their speaking skill. Trivedi and Bhargava (2010), Baghaei and Riasati (2013), and Ramezani, Larsari, and Kiasi (2016) have found the significant relation between the creativity and the students' achievement. Trivedi and Bhargava (2010) in their study found that adolesences who have high achievement have higher level of creativity than those who have low achievement.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Students who apply critical thinking skills tend to have thoughtful approach to their course, produce more challenging questions, and engage the pedagogical process profoundly (Murawski, 2014). Therefore, students who can make decision logically and confidently show better speaking performance (Sanavi & Tarighat, 2014;Ramezani, Larsari, & Kiasi, 2016;Bagheri, 2018). In other words, engineering students' critical thinking can be developed by applying problembased learning to encourage the improvement of speaking ability.…”
Section: Developing Engineering Students' Critical Thinking For Publimentioning
confidence: 99%